Pengaruh Word Of Mouth Terhadap Keputusan Pembelian Konsumen Pada Industri Perjalanan Wisata (Studi Kasus Pada CV. Tugu Citra Pesona Palembang) - Tuwandi Juniarto; Fahrurrozi Mawasandi (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
In the travel industry, word of mouth (WOM) plays an important role. Prospective tourists tend to seek information and recommendations from people close to them, such as family, friends, or colleagues, before deciding to travel (Litvin et al., 2008). This is because the tourism industry is an intangible sector, so WOM can help reduce the risk and uncertainty felt by prospective tourists (Jalilv and & Samiei, 2012). Structural Equation Modeling (SEM) is a statistical analysis technique used to build and test statistical models in the form of causal models (Anuraga, G. and Otok, B. W). From the development of the proposed model using the SEM method, the estimated strength of the relationship between various variables and significant indicators for success can be known. The model fit test in this report uses several criteria, including Chi Square, GFI, AGFI and RMSEA. Although the final model obtained a high Chi square value (149.247) with zero probability, but because several other criteria were met with GFI and AGFI values ​​above 0.9 and RMSEA below 0.08, the model was considered suitable. The results of this study indicate that word of mouth plays an important role in the tourism industry. Word of mouth has a significant influence on tourist purchasing decisions and customer loyalty. This is because the tourism industry is an intangible sector, so word of mouth can help reduce the risk and uncertainty felt by prospective tourists.